Apoptotic Potential of Polyphenol Extract of Mexican Oregano Lippia graveolens Kunth on Breast Cancer Cells MDA-MB-231 - Marilyn S. Criollo-Mendoza; José Basilio Heredia; Laura A. Contreras-Angulo; Israel García-Aguiar; Erick Paul Gutiérrez-Grijalva (Applied Sciences)
Some oregano species have been related to antiproliferative activity against various types of cancer cells, such as colon, liver, and breast; this has been mainly associated with their rich content of flavonoid-type compounds due to their ability to induce the activation of intracellular signaling pathways, such as apoptosis induction. This study aimed to determine the antiproliferative activity mechanism of the polyphenol extract of Mexican oregano (Lippia graveolens Kunth) on MDA-MB-231 breast cancer cells. The flavonoid content with the antiproliferative potential was quantified by ESI-QTOF-MS/MS chromatography, finding naringenin in a higher concentration (7758.71 µg/g extract) compared to the other identified compounds (quercetin, luteolin, and apigenin). Subsequently, the cytotoxicity of the extract was evaluated in the normal human fibroblasts CCD-18Co cell line, where the extract did not present cytotoxic activity at the evaluated concentration (150 µg/mL). In MDA-MB-231 cells treated with the same extract concentration, the activation of proteins associated with apoptosis was observed by western blot. Therefore, the previous antiproliferative activity shown by this extract on breast cancer cells may be due to the activation of this cell death pathway. Thus, the polyphenol extract of Mexican oregano L. graveolens has the potential for future research as an adjuvant in treating breast cancer.